Metabolic adaptation of myocardial mitochondria to mild altitude hypoxia - Gvozdjáková, A; Kucharská, J; Miklovicová, E; Rajecová, O; Gvozdják, J (International journal of cardiology, 1992)
We studied the metabolic parameters of myocardial mitochondria (respiration, respiratory control index, oxidative phosphorylation rapidity and coefficient of oxidative phosphorylation) in two groups of rats: one living at an altitude of 140 m above sea level (control group) and the other living from birth at an altitude of 1350 m above sea level for 2 and 4 months (experimental group). Compared with the control rats, the experimental rats during 2 and 4 months of mild altitude acclimatization increased their basal and stimulated respiration, as well as the rapidity of energy production by myocardial mitochondria. The coefficient of oxidative phosphorylation under mild altitude hypoxia decreased but the respiratory control index did not change. We explain these alterations of heart muscle metabolism at the mitochondrial level as an adaptation to the mild hypoxic conditions.
Keywords: krysa rodu Rattus; Animals; nadmořská výška; hypoxie; Oxidative Phosphorylation; srdeční mitochondrie; oxidativní fosforylace; mužské pohlaví; zvířata; Altitude; Hypoxia; Male; inbrední kmeny potkanů; Rats; Mitochondria, Heart; Rats, Inbred Strains